Evidence for Unruh's effect in hardon physics - Dey, Jishnu; Dey, Mira; Tomio, Lauro [UNESP]; Schiffer, Marcelo (Elsevier B.V., 1993)
In order that confinement should survive, light quarks inside hadrons have a very high acceleration and will feel a thermal bath with an Unruh temperature near 137 MeV. We show that this temperature is consistent with the experimentally observed departure from the Gottfried sum rule for the difference of the proton and neutron structure functions in deep inelastic electron scattering.